A revision of the neotropical genus Ocyolinus (Coleoptera: Staphylinidae: Staphylinini) - Chatzimanolis, Stylianos; Ashe, James S. (Zootaxa, 2009)
The Staphylinini genus Ocyolinus Sharp, 1884 is revised. Three species are described as new, O. astenos Chatzimanolis & Ashe sp. n., O. dimoui Chatzimanolis & Ashe sp. n. and O. nebulosus Chatzimanolis & Ashe sp. n., all from Panama. A lectotype is designated for O. rugatus Sharp, 1884 and O. vulneratus Bernhauer, 1906. Ocyolinus vulneratus Bernhauer is placed in synonymy with O. rugatus Sharp. Distribution maps, an identification key and illustrations of structural features are provided.